Codes of Good Governance in Hungary - Zsolt Bedo; Eva Ozsvald (Hungarian Academy of Sciences, Institute of Economics, 2008)
The purpose of the paper is to account for the short history of the soft law regulation of corporate conduct on the Budapest Stock Exchange (BSE). In theory, voluntary codes of good governance are expected to improve the deficiences of the existing mechanisms of corporate governance. In case of the Hungarian public companies the most important corporate governance problems are those related to the fragile safeguards of the interests of minority shareholders and to the lack of incentives for a much higher degree of transparency and disclosure. It is these two sets of issues on which the present analysis concentrates. The empirical core of the paper assesses the quality of information to be gained from the corporate governance reports of listed companies on the BSE. In order to discover links between the quality of information and firm characteristics we categorized the declarations based on their adequacy and applied binary regression analysis. We found inverse relationship between ownership concentration and the quality of information, while the higher liquidity of shares enhanced the adequacy of declarations.
Keywords: G18; G34; K22; P34; 330; Corporate governance; company law; voluntary codes of governance; Corporate Governance; Selbstverpflichtung; Informationswert; Ungarn